Comparison of the shock index, modified shock index, and age shock index in adult admissions to a tertiary hospital - David Sotello; Shengping Yang; Kenneth Nugent (The Southwest Respiratory and Critical Care Chronicles, 2019)
Background: Multiple variables interact constantly to maintain the hemodynamic status of patients. The shock index (SI), the modified shock index (MSI), and the age shock index (ASI) have been studied in different clinical settings to predict hemodynamic instability and associated outcomes. These indices are calculated from simple hemodynamic parameters, are non-invasive, and represent no additional expense. We wanted to analyze the performance of these three different indices in the patients admitted to our hospital.Methods: We performed a retrospective study in which we identified all adult patients (>18 years, <89 years) admitted to the University Medical Center in Lubbock, Texas, from 10/01/2015 until 9/30/2016. We collected basic clinical information, including age, initial blood pressure measurements, discharge diagnoses, length of stay (LOS), and mortality. With these variables we calculated for each patient the admission SI (defined as heart rate/systolic blood pressure), MSI (heart rate/mean arterial pressure), and ASI (age × SI). We separated the patients according to their admission diagnoses and calculated the median and 25th–75th percentiles for those parameters. We also compared mortality and LOS based on their admission SI using two different cutoff points at 0.7 and 1.0, their admission MSI (cutoff: 1.3), and their ASI (cutoff: 50).Results: A total of 18,478 adult patients admitted to our institution were included in this study. The median age was 53 years, the median LOS was 4 days, and the overall mortality was 3.8%. The median SI was 0.67; 43.3% of patients had an SI > 0.7 and 8.11% had an SI > 1.0. The median SI calculated for the patients with sepsis was 0.88; this was higher than the rest of admission diagnoses (p < 0.001). The mortality of the patients with an SI > 0.7 was 5.1% and with SI > 1.0 was 11.3% (p < 0.001). When comparing the MSI, those with an MSI > 1.3 had a mortality of 10.3%, and those with an ASI > 50 had a mortality of 10.0% (p < 0.001).Conclusions: The SI, MSI, and ASI are non-invasive calculations that may provide useful information when triaging patients early during admission. The diagnosis of sepsis results in a higher median SI, which may represent better prediction in outcomes compared with the rest of admission diagnoses. In our study, the three indexes performed equally. Since the SI with a cut-off of 1.0 identified patients with higher mortality risk, we would recommend using this cut-off instead of 0.7.Keywords: shock index, age shock index, modified shock index, outcomes